Synopsis of Bakeriella Kieffer, 1910 (Hymenoptera, Bethylidae) - Azevedo, Celso O. (Zootaxa, 2014)
Thirty valid species and their junior synonymous were investigated. Neotropical species of Epyrinae were also examined in order to find possible misclassified species of Bakeriella. Diagnoses and illustrations of all valid species are provided. Male genitalia of 14 previously described species are first described and illustrated. The lectotypes of Bakeriella flavicornis Kieffer, 1910 and Epyris montivagus Kieffer, 1910 are designated. The status of Bakeriella lindigi (Kieffer, 1910), stat. resurr. is resurrected from the synonyms of Bakeriella montivaga (Kieffer, 1910). The new synonymy is proposed for Bakeriella polita Evans 1964 =Bakeriella vicina Azevedo & Moreira, 2005, syn. nov.; Bakeriella lindigi Kieffer, 1910 =Epyris bogotensis Kieffer, 1910, syn. nov.; Bakeriella flavicornis Kieffer, 1910 =Bakeriella depressa Kieffer, 1910, syn. nov. Keys to males and females of Bakeriella are also provided. Twelve species had their distribution broadened.